PEEK/SiO2 composites with high thermal stability for electronic applications - Goyal, R. K.; Rokade, K. A.; Kapadia, A. S.; Selukar, B. S.; Garnaik, Baijayantimala (Electronic Materials Letters, 2013)
Thermal and mechanical properties of new high performance polymer matrix composites based on poly(etheretherketone) (PEEK) as matrix and crystalline-silica (SiO2) as reinforcement were discussed for application in electronic packaging substrates or printed circuit boards. The content of SiO2 was varied between 0 and 50 wt. %. Scanning electron microscopy showed uniform dispersion of SiO2 particles in the matrix. Thermogravimetry analysis showed significant increase in thermal stability and char yield with increase in SiO2 content in the matrix. Differential scanning calorimetry showed that SiO2 had a heterogeneous nucleating effect on PEEK, leading to an increase in peak temperature of crystallization and onset crystallization temperature of the composites compared to a pure matrix. The microhardness increased approximately 42%. A modified rule of mixtures with a strengthening efficiency factor equal to 0.06 fit the data nicely. The results show that the prepared PEEK/SiO2 composites may have potential applications in electronics.
Keywords: hardness; PEEK; polymer matrix composites; Thermal properties